2019
DOI: 10.1109/access.2019.2923660
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage Fault Tolerance Method for Large-Scale Manufacturing Network

Abstract: Nowadays, networked manufacturing paradigm, such as cloud manufacturing, has brought new challenges for fault tolerance methods. Failures and errors of manufacturing services are unavoidable in the large-scale network. Appropriate fault tolerance methods need to be adopted to improve the reliability of the whole manufacturing network. Aiming at solving this problem, a two-stage fault tolerance method is, thus, proposed. In the off-line stage, a LeaderRank-based manufacturing nodes ranking (LNR) algorithm is pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…If the server with the maximum reliability fails, then the task or VM executing on this server is scheduled at the server having the second-best reliability. A two-stage FT technique is presented by Wu, Y. et al (2019). In the first state, the authors have developed an algorithm to rank the services according to their significance.…”
Section: Related Workmentioning
confidence: 99%
“…If the server with the maximum reliability fails, then the task or VM executing on this server is scheduled at the server having the second-best reliability. A two-stage FT technique is presented by Wu, Y. et al (2019). In the first state, the authors have developed an algorithm to rank the services according to their significance.…”
Section: Related Workmentioning
confidence: 99%
“…As a result, LeaderRank has a faster convergence rate, higher stability for noisy data, and more robustness to manipulations (Li et al, 2014). LeaderRank is further applied to identify the influential nodes in complex products and systems (Li et al, 2019); in power grids (Zhou et al, 2019); in manufacturing services (Wu et al, 2019). Notably, in the field of "Library & Information Science", Xu et al (2020) found that LeaderRank had the best performance in ranking science and technology citation data, compared with other 17 network-based metrics.…”
Section: Pagerank and Leaderrankmentioning
confidence: 99%
“…Moreover, their method has largely eliminated the problems of user preferences and fault tolerance based on several parameters of service quality. Wu et al [29] employed replication strategies to achieve the trade-off between fault tolerance effect and fault tolerance loss. They proposed an A * -based heuristic alternative path searching (AHPS) algorithm to find suitable replacement schemes for composite services.…”
Section: Literature Reviewmentioning
confidence: 99%